2007
DOI: 10.2967/jnumed.107.043471
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Change in Human Nicotinic Acetylcholine Receptor After Smoking Cessation: 5IA SPECT Study

Abstract: Nicotinic acetylcholine receptors (nAChRs) are of great interest because they are implicated in various brain functions. They also are thought to play an important role in nicotine addiction of smokers. Chronic (2)-nicotine, a nAChR agonist, treatment in mice and rats elicits a dose-dependent increase in nAChRs in the brain. Upregulation of nAChRs in postmortem human brains of smokers has also been reported. However, changes in nAChRs after cigarette smoking cessation in humans are poorly understood. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 26 publications
10
60
2
1
Order By: Relevance
“…No associations between a 4 b 2 * nAChR densities and treatment type were found, but significant associations were discovered between the extent of a 4 b 2 * nAChR density reduction and the amount of decreased cigarette usage. These results indicate that a 4 b 2 * nAChR density is strongly linked to the number of cigarettes smoked per day, but not to the treatment type being administered, and are consistent with our previous study of untreated smokers (Brody et al, 2013) and other studies linking nicotine (Marks et al, 2011;Yates et al, 1995;Zhang et al, 2002) and cigarette smoke (Mamede et al, 2007;Mukhin et al, 2008;Staley et al, 2006;Wullner et al, 2008) exposure with upregulation of a 4 b 2 * nAChRs in brain regions other than the thalamus. Because education about the biological effects of smoking and quitting smoking are standard parts of smoking-cessation psychotherapy (Fiore et al, 2008), the additional information found here could prove useful in treatment of smokers by letting them know that brain receptor changes found with regular smoking tend toward normalization with smoking reduction and cessation.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…No associations between a 4 b 2 * nAChR densities and treatment type were found, but significant associations were discovered between the extent of a 4 b 2 * nAChR density reduction and the amount of decreased cigarette usage. These results indicate that a 4 b 2 * nAChR density is strongly linked to the number of cigarettes smoked per day, but not to the treatment type being administered, and are consistent with our previous study of untreated smokers (Brody et al, 2013) and other studies linking nicotine (Marks et al, 2011;Yates et al, 1995;Zhang et al, 2002) and cigarette smoke (Mamede et al, 2007;Mukhin et al, 2008;Staley et al, 2006;Wullner et al, 2008) exposure with upregulation of a 4 b 2 * nAChRs in brain regions other than the thalamus. Because education about the biological effects of smoking and quitting smoking are standard parts of smoking-cessation psychotherapy (Fiore et al, 2008), the additional information found here could prove useful in treatment of smokers by letting them know that brain receptor changes found with regular smoking tend toward normalization with smoking reduction and cessation.…”
Section: Discussionsupporting
confidence: 80%
“…ROIs were the prefrontal cortex, brainstem, and cerebellum, which were chosen for three reasons. First and most importantly, previous reports indicate that these ROIs (and most brain regions other than the thalamus) have upregulation of nAChR densities in cigarette smokers (Brody et al, 2013;Mamede et al, 2007;Mukhin et al, 2008;Staley et al, 2006;Wullner et al, 2008). Second, these ROIs have a range of 2-FA-binding levels from moderate to high (Brody et al, 2006;Brody et al, 2013;Kimes et al, 2008;Mukhin et al, 2008), which eliminates the issues of examining the highest nAChR density region (thalamus) as an experimental variable (because it does not have upregulation of nAChRs in smokers), and ROIs with very low nAChR density (eg, corpus callosum), which may have very small differences between groups or conditions.…”
Section: Pet Image Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…177 Upregulation following smoking cessation is time dependent, and 3 weeks later nAChRs were downregulated to the levels of nonsmokers. 178 The possible contribution of nAChR upregulation to the pathophysiology of ND is not fully understood, but is believed to be mediated by midbrain DA release. Vezina et al 168 have proposed that nicotine exposure produces temporary nAChR upregulation, leading to augmentation of midbrain dopaminergic neuron excitation and the induction of long-term potentiation.…”
Section: General Overviewmentioning
confidence: 99%